Clinical and mutational spectrum of highly differentiated, paired box 3:forkhead box protein o1 fusion–negative rhabdomyosarcoma: A report from the Children's Oncology Group. Issue 9 (20th February 2018) - Teot, Lisa A.; Schneider, Michaela; Thorner, Aaron R.; Tian, Jing; Chi, Yueh‐Yun; Ducar, Matthew; Lin, Ling; Wlodarski, Marcin; Grier, Holcombe E.; Fletcher, Christopher D. M.; van Hummelen, Paul; Skapek, Stephen X.; et al.
Abstract : BACKGROUND: Pediatric paired box 3:forkhead box protein O1 fusion–negative (PF–) rhabdomyosarcoma (RMS) represents a diverse spectrum of tumors with marked differences in histology, myogenic differentiation, and clinical behavior. METHODS: This study sought to evaluate the clinical and mutational spectrum of 24 pediatric PF– human RMS tumors with high levels of myogenic differentiation. Tumors were sequenced with OncoPanel v.2, a panel consisting of the coding regions of 504 genes previously linked to human cancer. RESULTS: Most of the tumors (19 of 24) arose at head/neck or genitourinary sites, and the overall survival rate was 100% with a median follow‐up time of 4.6 years (range, 1.4‐8.6 years). RAS pathway gene mutations were the most common mutations in PF–, highly differentiated RMS tumors. In addition, Hedgehog (Hh) and mechanistic target of rapamycin (mTOR) gene mutations with evidence for functional relevance (high‐impact) were identified in subsets of tumors. The presence of Hh and mTOR pathway gene mutations was mutually exclusive and was associated with high‐impact RAS pathway gene mutations in 3 of 4 Hh‐mutated tumors and in 1 of 6 mTOR‐mutated tumors. CONCLUSIONS: Interestingly, Hh and mTOR gene mutations were previously associated with rhabdomyomas, which are also known to preferentially arise at head/neck and genitourinary sites. Findings from this study further support the idea that PF–, highly differentiated RMS tumors and rhabdomyomas may represent a continuous spectrum of tumors. Cancer 2018;124:1973‐81 . © 2018 American Cancer Society . Abstract : Highly differentiated rhabdomyosarcomas contain frequent, high‐impact RAS, Hedgehog, and mechanistic target of rapamycin pathway gene mutations. They may form a continuous spectrum of tumors with rhabdomyomas.